MARKET ECONOMY AND ITS IN THE COUNTRY HELD PLACE (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
It is known in society each one of the system own is important . Market economy this different different to ownership based on economic is a system . This is the system society and state in his life enough important has. This system to freedom based on His basis entrepreneurship organize is enough Market economy about information this in my article briefly statement I did